"Is it cancer or not?" A qualitative exploration of survivor concerns surrounding the diagnosis and treatment of ductal carcinoma in situ. Issue 8 (22nd February 2022) - Rosenberg, Shoshana M.; Gierisch, Jennifer M.; Revette, Anna C.; Lowenstein, Carol L.; Frank, Elizabeth S.; Collyar, Deborah E.; Lynch, Thomas; Thompson, Alastair M.; Partridge, Ann H.; Hwang, E. Shelley
Abstract : Background: Of the nearly 50, 000 women in the United States who undergo treatment for ductal carcinoma in situ (DCIS) annually, many may not benefit from treatment. To better understand the impact of a DCIS diagnosis, patients self‐identified as having had DCIS were engaged regarding their experience. Methods: In July 2014, a web‐based survey was administered through the Susan Love Army of Women breast cancer listserv. The survey included open‐ended questions designed to assess patients' perspectives about DCIS diagnosis and treatment. Deductive and inductive codes were applied to the responses; common themes were summarized. Results: Among the 1832 women included in the analytic sample, the median age at diagnosis was 60 years. Four primary themes were identified: 1) uncertainty surrounding a DCIS diagnosis, 2) uncertainty about DCIS treatment, 3) concern about treatment side effects, and 4) concern about recurrence and/or developing invasive breast cancer. When diagnosed, participants were often uncertain about whether they had cancer or not and whether they should be considered a "survivor." Uncertainty about treatment manifested as questioning the appropriateness of the amount of treatment received. Participants expressed concern about the "cancer spreading" or becoming invasive and that they were not necessarily "doing enough" to prevent recurrence. Conclusions: In a large, national sample, participants with a history of DCIS reported confusion and concern about the diagnosis and treatment, which caused worry and significant uncertainty. Developing strategies to improve patient and provider communications regarding the nature of DCIS and acknowledging gaps in the current knowledge of management options should be a priority. Abstract : Ductal carcinoma in situ (DCIS) survivors often report feelings of uncertainty and concern about their diagnosis and treatment. Developing strategies to improve communication regarding the nature of DCIS as well as the potential benefits and harms of different DCIS management options should be a priority.